Isolation of Penicillium strains from the mangrove forests of the Northern coastal region with high potential for mycophenolic acid production for pharmaceutical applications - Pham, Thanh Huyen; Nguyen, Huy Hoang; Bach, Thi Mai Hoa; Dang, Thi Thuy Duong; Le, Thi Minh Thanh; Nguyen, Hong Nhung; Nguyen, Phuong Nhue (Vietnam Journal of Biotechnology, 2025)
Penicillium is known as a genus of fungi that is widely distributed throughout the environment and found all over the world. The Penicillium genus is found both on land and in coastal mangrove areas, where it exists on various parts of plants and animals, playing roles in symbiosis and the decomposition of organic matter. Coastal mangrove forests are highly regarded for the diversity of their microbial populations, especially fungal species. Previous studies have shown that marine fungal strains contain many potential bioactive compounds that may be utilized in the pharmaceutical, cosmetic, and food industries. Compounds derived from fungal strains originating in coastal mangrove areas have commercial value and demonstrate greater potential for research and the production of new drugs compared to those isolated from terrestrial environments. Among them, marine fungal strains of the genus Penicillium have been shown to exhibit novel biological activities, particularly those with significant medical applications, such as antibiotics, antifungal, anti-inflammatory, anticancer agents, and immunosuppressants for preventing organ transplant rejection. In the context of the developing healthcare sector and the growing demand for organ transplants in the country, there is a priority to actively produce mycophenolic acid (MPA) from domestic sources. Therefore, this study reports the isolation of 24 Penicillium strains from the Northern coastal region, which exhibit high potential for mycophenolic acid biosynthesis, with a focus on production for pharmaceutical applications in Vietnam.